Pathology of gastro-intestinal discorders in piglets - Smitha S (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 2003)
The present study was undertaken to assess the prevalence and pathological disorders of the gastro-intestinal system of piglets. The results of the present investigation and evaluation of the data from the records revealed a high incidence of gastro-intestinal disorders to the level of eighty eight per cent. A detailed systematic examination of fifty piglet carcasses brought for autopsy during the period of investigation was conducted and the gross and histopathological lesions were studied in detail and were classified based on age and sex. Higher incidence of gastro-intestinal lesions was recorded in piglets \ aged 10-20 days and their possible causes are described. Vascular and degenerative changes were the predominant lesions, followed by inflammation. Among the inflammatory changes, catarrhal gastro-enteritis was the most prevalent lesions observed. Escherichia coli and Klebsiella were isolated from such cases and are suspected as the possible pathogenesis has been described. Viral etiology was also suspected in certain cases as the infiltrating cells appeared predominantly Iymphocytes. Besides these ulcers were recorded in the stomach and the intestinal tract. Salmonella cholerae suis was isolated from the intestinal ulcers. Bacterial isolations were obtained in the intestine, liver, heart blood and sow's milk. A total of 17 bacterial isolations were obtained from 11 animals. Their role in the causation of gastro-intestinal disorders have been explained. Coincident with various gastro-intestinal disorders, liver of 30 cases and mesenteric lymph nodes of 28 cases revealed variety of vascular, degenerative and inflammatory lesions. In one case 'with suppurative hepatitis, Salmonella cholerae suis was isolated. The variable degrees of lymphoid depletion, degeneration and necrosis of lymphoid follicles of mesenteric lymph nodes and the Iymphocytes of Peyer's patches indicated immunosuppression. The vascular and degenerative lesions, without any evidence for infections etiology observed in the gastro-intestinal tract and liver suggested the involvement of some toxic factors. Further the higher incidence of the disorders in the young ones, the isolation mostly of the resident flora of the intestinal tract and the lymph node changes indicated the necessity for an in depth study on the role of factors like immune status of the animals and eo-pathogens in the causation of gastro- intestinal disorders in piglings,